Better diastolic function in CRT candidates is associated with improved survival after CRT implantation. (25th November 2020) - Galli, E; Smiseth, O.A; Aalen, J; Duchenne, J; Larsen, C; Sade, E; Hubert, A; Anilkumar, S; Penicka, M; Hernandez, A; Leclercq, C; Voigt, J.-U; et al.
Abstract: Background: The relationship between diastolic dysfunction (DD) and outcome after CRT is debated. Purpose: Purpose of this study was to evaluate the role of DD in predicting all-cause mortality in heart failure patients undergoing CRT. Methods: One-hundred ninety-three patients (age: 67±11 years, QRS width: 167±21 ms, LVEF 28±8%) were included in this multicentre prospective study. Mitral filling pattern, mitral tissue Doppler velocity, tricuspid regurgitation velocity, and indexed left atrial volume were used to classify DD from grade I to III according to the 2016 recommendations of the American Society of Echocardiography/European Association of Cardiovascular Imaging. A reduction of LV end-systolic volume >15% at 6-month follow-up (FU) identified CRT-responders and was observed in 132 (68%) patients. Results: During a median 35 months FU, 29 (15%) patients died. Through multivariable analysis, coronary artery disease, NYHA functional class and grade I DD were shown to be independent predictors of prognosis (Table 1). Grade I DD was associated with a longer survival rate in both responders and non responders (Figure 1). Non responders with grade II-III DD had the worse outcome (HR 12.5 [3.56–44.04], p<0.0001). Conclusions: Better diastolic function at baseline is associated with an improved survival after CRT implantation, independently of CRT-response. Funding Acknowledgement: Type of funding source: None